2018
DOI: 10.1103/physrevlett.121.137203
|View full text |Cite
|
Sign up to set email alerts
|

Level Attraction Due to Dissipative Magnon-Photon Coupling

Abstract: We report dissipative magnon-photon coupling caused by cavity Lenz effect, where the magnons in a magnet induce a rf current in the cavity, leading to a cavity back action that impedes the magnetization dynamics. This effect is revealed in our experiment as level attraction with a coalescence of hybridized magnon-photon modes, which is distinctly different from level repulsion with mode anticrossing caused by coherent magnon-photon coupling. We develop a method to control the interpolation of coherent and diss… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

13
224
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 302 publications
(249 citation statements)
references
References 41 publications
13
224
2
Order By: Relevance
“…Recently, a number of experiments [47][48][49][50] suggest the quasiparticles energyies Re[E] can cross each other in non-Hermitian systems, instead of anti-crossing universally arising in all Hermitian Hamiltonians. This remarkable phenomenon is termed as level attraction [51].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, a number of experiments [47][48][49][50] suggest the quasiparticles energyies Re[E] can cross each other in non-Hermitian systems, instead of anti-crossing universally arising in all Hermitian Hamiltonians. This remarkable phenomenon is termed as level attraction [51].…”
Section: Introductionmentioning
confidence: 99%
“…Experimentally, people often avoid placing magnetic samples at rf magnetic (h-) field nodes of a cavity mode, as here coherent magnon-photon coupling vanishes. However, dissipative coupling could dominate near this condition, where the cavity Lenz effect produces a microwave current that impedes the magnetization dynamics [25]. Instead of level repulsion with mode anticrossing seen in coherently coupled magnon-photon systems, dissipative coupled systems exhibit level attraction with a coalescence of hybridized magnon-photon modes [25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…However, dissipative coupling could dominate near this condition, where the cavity Lenz effect produces a microwave current that impedes the magnetization dynamics [25]. Instead of level repulsion with mode anticrossing seen in coherently coupled magnon-photon systems, dissipative coupled systems exhibit level attraction with a coalescence of hybridized magnon-photon modes [25][26][27]. Alternatively, Grigoryan and Xia have proposed an approach to explore level attraction [28] in hybrid magnon-photon systems, by modulating the relative phase [29] between coherent microwaves, and very recently Boventer et al [30] reported level attraction in these systems.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations